Florística e estrutura de vegetações ciliares no alto da bacia hidrográfica no rio Paraguaçu, Mucugê, Bahia, Brasil - Martins, Carla Tatiana de Vasconcelos Dias (2015)
The present study aimed to contribute to the knowledge of the vascular flora of riparian vegetation on top of the basin in the river Paraguaçu. In this basin, it was performed the characterization of the composition and structure of riparian fragments of the Upper Paraguaçu River and of the Sertãozinho Stream in Mucugê - BA. For the floristic survey, field expeditions were carried out monthly, from September 2013 to May 2014, during which it was collected samples of fertile specimens in transects along the river, in a range of 50 meters wide. For the phytosociological analysis it was used the Point-centred Quarter Method (102 points for each area) in 17 transects, considering all the woody individuals, with stem diameter at ground level (DGL) ≥ 3 cm and height above 1.30 m. The floristic results were compared with other areas of riparian vegetation of the Chapada Diamantina and analysis of the structure of the vegetation was performed using the program Fitopac. I was recorded 117 species at the Upper Paraguaçu River and 83 at Sertaozinho stream, with 21 common to both environments. Among the families registered with the highest species richness, Fabaceae and Asteraceae were common to both sites. In riparian vegetation at Upper Paraguaçu River Vochysia pyramidalis was considered one of the most abundant species, while in Sertãozinho Stream, Paralychnophora harleyi (H.Rob.) D.J.N. and Senna cana (Nees & Mart.) H.S.Irwin & Barneby are among the most significant in number of individuals. Regarding the importance value index (IVI), the other species are among the ten most significant in both studied areas. The floristic composition of the Upper Paraguaçu River showed greater wealth than the Sertaozinho stream. The analysis of similarity between the surveys of riparian vegetations of the Chapada Diamantina revealed the formation of two groups with low similarity (≤ 16%). The riparian vegetation found at the top of the watershed of Paraguaçu River showed distinct physiognomies, being one of riparian vegetation and other of transition between riparian vegetation and rocky fields. The concentration of individuals in the initial diameter classes indicated that the area is found in intermediate stage of succession. Furthermore, there was the presence of areas with monodominance and high wealth of ruderal species. Despite the anthropic process found, the studied area had a high local diversity when compared with other studies conducted in the region. The composition of the vegetation in the Sertãozinho Stream proved to be diversified with the occurrence of rare and endangered species. These same areas when compared to other riparian vegetation in the Chapada Diamantina showed low similarity, reinforcing the argument that even geographically close vegetations can have distinct floristic composition, showing a high heterogeneity.